2021
DOI: 10.1371/journal.pone.0247893
|View full text |Cite
|
Sign up to set email alerts
|

Soil respiration variation along an altitudinal gradient in the Italian Alps: Disentangling forest structure and temperature effects

Abstract: On the mountains, along an elevation gradient, we generally observe an ample variation in temperature, with the associated difference in vegetation structure and composition and soil properties. With the aim of quantifying the relative importance of temperature, vegetation and edaphic properties on soil respiration (SR), we investigated changes in SR along an elevation gradient (404 to 2101 m a.s.l) in the southern slopes of the Alps in Northern Italy. We also analysed soil physicochemical properties, includin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 108 publications
1
6
0
Order By: Relevance
“…For example, pH can be spatially variable if different tree species have litter with various levels of calcium concentration, directly affecting soil acidity (Reich et al, 2005). In combination, it is currently under debate whether and how structural vegetation properties modulate the effects of light‐induced soil properties (Badraghi et al, 2021). Laboratory incubation studies have shown that processes affecting soil nutrient status are influenced by an interaction between litter quality and temperature (Fierer et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, pH can be spatially variable if different tree species have litter with various levels of calcium concentration, directly affecting soil acidity (Reich et al, 2005). In combination, it is currently under debate whether and how structural vegetation properties modulate the effects of light‐induced soil properties (Badraghi et al, 2021). Laboratory incubation studies have shown that processes affecting soil nutrient status are influenced by an interaction between litter quality and temperature (Fierer et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although these interaction effects may be partly related to design in our case, the discussion calls for future research on the relative importance of plant litter quality and light intensity in mountainous temperate forest soils (Badraghi et al, 2021), where both effects should be experimentally separated to improve our understanding on that matter.…”
Section: Structurally Complex Forests Create Heterogeneity In Resourc...mentioning
confidence: 97%
“…the effects of variations of soil properties and of temperature across altitudinal gradients, since both vary along the altitudinal gradient (Badraghi et al 2021). Pineda et al (2021) reported a data set of soil-air emissions of CO 2 in Ecuadorian Andes along an altitudinal gradient (3000-400 m).…”
Section: Comparison With Floodplain Lakes In Central Amazonmentioning
confidence: 99%
“…Similarly, higher solar radiation intake on infested sites leads to rising soil and air temperatures on plots with bark beetle-infested trees [33]. SR follows seasonal dynamics of soil temperature with water surplus throughout the year [41], as it depends on both factors, with soil temperature having a more dominant effect [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…There are studies that focus on SR within a vertical gradient [43,55,56] and studies that examine SR after windthrow or bark beetle attacks [22,42,49,57]. However, these studies do not address how different elevation zones of mountain spruce forests respond to disturbance events in terms of SR.…”
Section: Introductionmentioning
confidence: 99%